Comparison of the Elution and Absorption of Picornaviruses by Cotton and Calcium Alginate Wool Swabs - Phillips, C. Alan (1965)
The recovery of picornaviruses by cotton and calcium alginate wool swabs was studied by use of prototype strains of poliovirus 1, echovirus 1, coxsackievirus A9, and rhinovirus 16/60. No significant differences in recovery of viruses by the two types of swabs could be demonstrated. It is suggested that use of cotton swabs in the virus laboratory be continued, since wool swabs may favor the recovery of undesirable bacterial contaminants. Adsorption of viruses by cotton and wool swabs was similar from virus-buffer mixtures at pH 4.0, 7.0, and 8.0 at 24 and 37 C. Elution of virus from cotton and wool swabs was also studied. There was no significant difference in the amount of virus eluted at pH 5.5, 7.1, or 8.4.